Relationships between field tests of power and athletic performance in track and field athletes specializing in power events - Aoki, K.; Kohmura, Y.; Sakuma, K.; Koshikawa, K.; Naito, H. (International Journal of Sports Science and Coaching, 2015)
We investigated the relationships between power event scores and power/strength tests using the International Association of Athletics Federations (IAAF) scoring table. We sought to identify tests suitable for evaluating the performance of athletes specialized in power events involving different techniques (jumping, sprinting, and throwing). Seventy-four male university-level track and field athletes participated in this study. Standing triple jump, standing quintuple jump, and backward medicine ball throwing were positively correlated with IAAF scores in sprinters (p < 0.05), while forward medicine ball throwing, backward medicine ball throwing, and clean lift (p < 0.05) were associated with IAAF scores in throwers. Standing long jump (p < 0.05), standing triple jump, standing quintuple jump, and anaerobic power (p < 0.001) were positively correlated with IAAF scores in all athletes. Our results demonstrated that standing triple jump and standing quintuple jump were effective indicators of performance in power events in university-level athletes.